2011
DOI: 10.1007/s10107-011-0455-1
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional lattice-free cuts and asymmetric disjunctions for mixed-integer polyhedra

Abstract: In this paper, we study the relationship between 2D lattice-free cuts, the family of cuts obtained by taking two-row relaxations of a mixed-integer program (MIP) and applying intersection cuts based on maximal lattice-free sets in R 2 , and various types of disjunctions. Recently, Li and Richard (2007) studied disjunctive cuts obtained from t-branch split disjunctions of mixed-integer sets (these cuts generalize split cuts). Balas (2009) initiated the study of cuts for the two-row continuous group relaxation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…The cross disjunction (see Dash et al (2012a)) associated to π 1 , π 2 ∈ Z n 1 \ {0}, and γ 1 , γ 2 ∈ Z, is given by…”
Section: Cross Disjunctions and Cross Cutsmentioning
confidence: 99%
“…The cross disjunction (see Dash et al (2012a)) associated to π 1 , π 2 ∈ Z n 1 \ {0}, and γ 1 , γ 2 ∈ Z, is given by…”
Section: Cross Disjunctions and Cross Cutsmentioning
confidence: 99%
“…Dash, Dey and Günlük, [38] proved an intriguing result for model (3) when |B| = p = 2. They showed that corner(B) is defined entirely by disjunctive cuts from crooked cross disjunctions of the form {x ∈ R 2 : π 1 x ≤ π 1 0 , (π 2 − π 1 )x ≤ π 2 0 − π 1 0 } ∨ {x ∈ R 2 : π 1 x ≤ π 1 0 , (π 2 − π 1 )x ≥ π 2 0 − π 1 0 + 1} ∨ {x ∈ R 2 : π 1 x ≥ π 1 0 + 1, π 2 x ≤ π 2 0 } ∨ {x ∈ R 2 : π 1 x ≥ π 1 0 + 1, π 2 x ≥ π 2 0 + 1} where π 1 , π 2 ∈ Z 2 and π 1 0 , π 2 0 ∈ Z.…”
Section: Theorem 84 For Any α > 1 There Is a Choice Of Data In (3)mentioning
confidence: 99%
“…. , 4, then it is called a CC cut for P obtained from the disjunctionD(π 1 , π 2 , γ 1 , γ 2 ), see [3]. In other words a linear inequality is called a CC cut if it is valid for P LP \ int(C).…”
Section: Introductionmentioning
confidence: 99%
“…The extension of D(π 1 , π 2 , γ 1 , γ 2 ) is defined to beD(π 1 , π 2 , γ 1 , γ 2 ) = {(x, y) ∈ R n 1 +n 2 : x ∈ D(π 1 , π 2 , γ 1 , γ 2 )} and it is called a crooked cross (CC) disjunction for Z n 1 × R n 2 , see [3]. The extensions of the sets in (1)- (4), are defined similarly and each such extension is called an atom of the disjunctionD(π 1 , π 2 , γ 1 , γ 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation